2018
DOI: 10.1055/s-0038-1649520
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Microvascular Flap Selection for Anterior Cranial Fossa Reconstruction

Abstract: In our experience, osteocutaneous flaps (especially the OCRFFF) are preferred for complete autologous reconstruction of high and middle ACF defects. Low skull base defects are more difficult to reconstruct, and consideration of free muscle flaps (no bone) should be weighed as an option in this anatomic area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…Cranioplasty through titanium, ceramic, or plastic implants is among the most frequently employed strategies, and most invariably requires a two-stage surgery [ 120 ]. Autogenous calvarial grafts [ 121 ] or free flaps [ 122 , 123 , 124 ] have also been described to reconstruct defects of the frontal bone.…”
Section: Treatmentmentioning
confidence: 99%
“…Cranioplasty through titanium, ceramic, or plastic implants is among the most frequently employed strategies, and most invariably requires a two-stage surgery [ 120 ]. Autogenous calvarial grafts [ 121 ] or free flaps [ 122 , 123 , 124 ] have also been described to reconstruct defects of the frontal bone.…”
Section: Treatmentmentioning
confidence: 99%
“…The risk of bias assessment was performed on the studies chosen for inclusion in the analysis, which excluded 1 study, resulting in a total of 13 articles included in the final analysis (Figure 1). 18,25‐36 …”
Section: Resultsmentioning
confidence: 99%
“…Many authors advocate for the routine use of vascularized tissue for reconstruction of the ventral skull base 2,18,19 . Some recent studies have found that a history of pre‐ or post‐operative radiation has no significant impact on the success of skull base reconstruction 11,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…One should consider performing sinus surgery in the primary or secondary setting for these patients, which helps assist in monitoring for local recurrence and also prevents the sequela of post-radiation sinusitis. A Rains stent can be placed in the frontal outflow tract to prevent scarring during radiation treatment [22] . Low volume flaps risk nasocutaneous fistulas, which can occur due to numerous factors, including contact with contaminated paranasal sinuses, the effects of gravity, and adjuvant radiation therapy.…”
Section: Anterior Skull Basementioning
confidence: 99%